UJIAN BERBASIS KOMPUTER (UBK): Studi Kasus Penyelenggaraan Ujian - Amalia Sapriati; Minrohayati Minrohayati (LPPM Universitas Terbuka, 2009)
Universitas Terbuka (UT) is an Open and Distance University in Indonesia. Since 2004, UT had developed a system for computer-based examination (UBK). This system was presented firstly on 2007. This paper addresses UT experience in conducting computer-based examination,The purpose of this research is to describe the implementation of the exam system and to identify problems which arose during implementation. Data is collected based on the student responds of the questionnaire, interview and the observer report. Data was collected in May and November 2008. 31 respondents were the students who registered and took computer-based examination at four Regional Offices in UT. Quantitative data were analyzed by using SPSS 15.0 for Windows. The results of the research revealed that (1) the main reason students took computer based examination was to improve their grades, (2) the students reported that they have good enough competencies in basic computer skills. In addition they described that they have registered computer based examination online by themselves, (3) the implementation of at their regional offices was good, (4) however students expected that there should be quality improvement in this kind of examination, especially in aspects of exam socialization, information, quota and session of student examination.